Childhood socioeconomic circumstances and adult height and leg length in central and eastern Europe. Issue 4 (13th March 2008) - Webb, E; Kuh, D; Peasey, A; Pajak, A; Malyutina, S; Kubinova, R; Topor-Madry, R; Denisova, D; Capkova, N; Marmot, M; Bobak, M
Abstract : Background: Adult height and leg length have been shown to be positively associated with childhood socioeconomic circumstances in several studies in western populations. This study will determine whether similar associations are observable in settings with different social histories, and will assess whether adult leg length is more strongly associated than adult height. Methods: Random samples of men and women aged 45–69 years were taken from population registers in Novosibirsk (Russia), Krakow (Poland) and six towns of the Czech Republic, recruiting nearly 29 000 people. Participants completed a questionnaire that included questions regarding their mother's and father's education (not available in the Czech Republic) and ownership of several household items when they were 10 years old. Participants' standing and sitting heights were measured and from these an estimate of leg length was derived. Associations between indicators of childhood socioeconomic circumstances and anthropometric measures were analysed using linear regression. Results: Russian individuals were shorter and reported fewer household assets at the age of 10 years than Czech and Polish individuals. Parental education and household assets were strongly associated with each other and both were independently associated with height, leg length and trunk length. Height was associated with childhood circumstances more strongly than leg length. The associations of childhood circumstances with the leg/trunk ratio were weak and inconsistent. Conclusion: In these urban populations in eastern Europe, adult height is associated with childhood conditions at least as strongly as leg length.